Preloved Shoes E-Store - Sautan, Nurul Izzatie; Hassan, Norlida (Applied Information Technology And Computer Science, 2024)
Electronic commerce (E-commerce) has made it simpler for people to eliminate physical work and save time compared to conventional commerce, which is carried out physically with a person’s effort to travel and collect items. Ilham Bundle Shoes is a company that sells a selection of shoes that have been previously owned or well-known as preloved items. Preloved Shoes E-store is a web-based system that improves the quality of the existing system at Ilham Bundle Shoes by using a more advanced store management and ordering system. Customers at Ilham Bundle Shoes still have to physically purchase shoes using a manual approach, which means they must message the business over WhatsApp to make a purchase and receive payment in cash. As a result, this system was created especially for the proprietors and patrons of these shoe retailers. The system may then be operated more methodically, reducing the amount of time needed to record and update order information and increasing customer satisfaction. The system is designed using a structured approach, and the model used is a Prototype model as each phase is compatible with system development. In addition, this system is developed using Visual Studio Code software and MySQL server to store data in the database. Finally, it is expected that the Preloved Shoes E-store can be used optimally and benefit the owner store to view weekly sales reports. Besides, can improve efficiency in carrying out shoe management processes effectively.